2011
DOI: 10.1590/s1808-86942011000400019
|View full text |Cite
|
Sign up to set email alerts
|

Bedside assessment of swallowing in elderly subjects using psychotropic drugs

Abstract: Neurol eptic drugs are used in several mental disorders, but are suspected of causing oropharyngeal dysphagia, mainly in the elderly. Aim:To study the effect of neuroleptic agents on swallowing of institutionalized older people. Material and method:A cross sectional study of swallowing in 47 subjects that either used or did not use neuroleptic drugs. Bedside swallowing tests with foods of four different consistencies were carried out.Results: There was no significant difference between the two groups. Users of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the paper by Roque et al 16 , it was observed that the most used drugs were neuropsychiatric and antihypertensive, interfering in the swallowing dynamics of the elderly. Fioravanti et al 17 observed the interference of psychotropic drugs in the process of deglutition of 47 elderly residents of a nursing home. The signs suggestive of dysphagia were evaluated in two groups of elderly people: those who used neuroleptic drugs and the group that did not use this type of medication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the paper by Roque et al 16 , it was observed that the most used drugs were neuropsychiatric and antihypertensive, interfering in the swallowing dynamics of the elderly. Fioravanti et al 17 observed the interference of psychotropic drugs in the process of deglutition of 47 elderly residents of a nursing home. The signs suggestive of dysphagia were evaluated in two groups of elderly people: those who used neuroleptic drugs and the group that did not use this type of medication.…”
Section: Literature Reviewmentioning
confidence: 99%